Impacts of multi-gate regulator operation schemes on local scour downstream. Issue 1 (2nd January 2021) - Elsayed, Hamdy; Helal, Esam; El-Enany, Moustafa; Sobeih, Mohamed
ABSTRACT: Regulators are commonly used to control and measure flows in streams and irrigation canals. Inadequate operation of regulator gates may lead to scour downstream, possibly leading to structural failure. An experimental work was conducted to study the effect of different regulator gate operation schemes on scour hole formation downstream under free-flow conditions. The experimental model consisted of five sluice gates, a solid apron, and a mobile bed (sand). One hundred and thirty-five different gate operation schemes were studied by changing the number of opened gates and the gate arrangement with different hydraulic conditions. The parameters considered in this study were the downstream Froude number, tail water depth, upstream water head, and the number of opened gates and their arrangements. A dimensional analysis was applied to obtain non-dimensional quantities that describe the different variables affecting scour downstream the gates. The obtained results of the experimental tests were analysed and graphically represented. It was observed that the number of opened gates and their arrangements had significant effects on the scour hole pattern under different hydraulic conditions. The most favourable operation case was with all five open gates opened, while the least favourable operation case was with only the side gate opened.